Prevalence of Fowl Adenovirus Infection in Broilers and Kadaknath Birds in Malwa Region of Madhya Pradesh - Shrivastava, Nidhi; Shukla, Supriya; Chhabra, Daljeet; Jatav , G.P.; Mehta, H.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A study was conducted to study the prevalence of Fowl adenovirus infections in broilers and Kadaknath birds in Malwa region of Madhya Pradesh during July 2016- March 2017. Overall 2.78% mortality was recorded at 30 broiler farms. Total mortality recorded at Kadaknath farms was 6.84%. Age-wise highest mortality in broiler farms was recorded at 3rd week of age and highest mortality was recorded at 1st week and 3rd week of age respectively at Mhow and Jhabua kadaknath farms. Disease-wise highest mortality in broilers was recorded due to IBH-HPS (1.6%) followed by colibacillosis. At Kadaknath farm Mhow and Jhabua maximum mortality was recorded due to yolksac infection (2.83%) and coccidiosis (1.90%) respectively.
Keywords: IBH-HPS; prevalence; broilers; Kadaknath; Malwa region; FAdV